PATIENTS’ AND NURSES’ PERCEPTIONS OF PALLIATIVE CARE OUTCOMES: A COMPARATIVE STUDY - Dewiyuliana Dewiyuliana; Sri Warsini; Christantie Effendy (Belitung Nursing Journal, 2019)
Background: Patients with advanced cancer require treatment and the fulfillment of their needs, based on the results of assessments regarding their physical symptoms, psychological and spiritual needs. Palliative care should be delivered with a person-centered care approach. It is important to consider the patients’ reports of their carings’ outcomes. Comparisons between the patients’ and nurses’ perceptions of palliative care outcomes can be used to improve the quality of palliative care. Objective: The purpose of this study is to compare the patients’ and nurses’ perceptions of palliative care outcomes during the patients’ hospitalization. Methods: This is a comparative descriptive study with a cross-sectional design. Data were collected from May to June 2018 from a total of 106 patients with advanced cancer, and 61 nurses. The versions of the Palliative care Outcome Scale (POS) for patients and nurses were used to measure the palliative care outcomes of the patients’ and nurses’ perceptions. Result: The study found a significant difference between the perceptions of the patients and nurses for the palliative care outcomes, particularly in the information availability domain (p = 0.001), the other symptoms domain (p = 0.029), and the anxiety feelings domain (p = 0.030), while the other seven domains had no significant differences between both groups (p > 0.05). Conclusion: The anxiety feelings, other symptoms and information availability domains are the aspects of palliative care which need more attention from health care providers, especially nurses, when caring for patients with advanced cancer.